Impact of three light smoltification regimes on the performance and genetic parameters of traits in Atlantic salmon - Gjerde, Bjarne; Boison, Solomon Antwi; Hazlerigg, David; Ytrestøyl, Trine; Mørkøre, Turid; Jørgensen, Even; Striberny, Anja; Sandve, Simen Rød (Frontiers in Animal Science, 2025)
IntroductionThis study investigates the impact of three different light regimes prior to seawater transfer on growth, survival, wounds, and losers in Atlantic salmon during a ten-month period in a net-cage in the sea.MethodsA total of 3,000 Atlantic salmon pre-smolts from 100 families were tagged with passive integrated transponders (PIT) and distributed across six tanks, with duplicated tanks exposed to a different light regime: 6 weeks on 8-hour light (L)/16-hour dark (D), 12L:12D, and 24L:0D, followed by 6 weeks on 24L:0D. One week prior to seawater transfer in June 2021, body weights and external smolt status were recorded. Body weights, wounds, and losses were recorded 135 days after seawater transfer in November 2021, and body weights were recorded again 300 days after seawater transfer in April 2022. A binary survival trait was defined for the seawater periods: Period 1 (day 0 to day 135) and Period 2 (day 136 to day 300), along with the time to death for the fish that were collected as dead.ResultsBody weight in June 2021 and time to death in Period 1 were the only traits significantly affected by the light regime. Fish on the 24L:0D regime were, on average, 10.0% and 12.2% heavier than those on the 12L:12D and 8L:16D regimes, respectively. They also died, on average, 15.7 and 17.7 days earlier than those on the 12L:12D and 8L:16D regimes. During the first two months in seawater, mortality was higher for fish on the 24L:0D regime, with an accumulated mortality of 8.8%, compared to 0.7% and 1.0% for those on the 8L:16D and 12L:12D regimes, respectively. Mortality in Period 2 was similar across the three light regimes. Most traits had moderate heritability, but heritability was low for healthy fish and fish with wounds in November 2021, as well as for survival and time to death in Period 1. There was negligible genotype-by-light regime interaction. Genetic correlations between survival and the other traits were low to medium, and not significantly different from zero.DiscussionWhile light regimes did not significantly affect growth during the seawater period, they did influence survival, particularly during the first two months in seawater. The estimated genetic parameters suggest that direct selection for increased growth and survival during the early seawater phase may be more effective for improving seawater performance than indirect selection based on the studied smolt-indicator traits.ConclusionThe findings indicate that direct selection for increased growth and survival during the early seawater period offers promising prospects for enhancing seawater performance.